Undocumented Migrant Worker’s Human Right: Should be Protected? International Law and Trafficking Law Perspective - NURISKANDAR, LALU HENDRI (STIS Darussalam Bermi, 2022)
Undocumented Migrant Workers violate immigration rules and can be detrimental to the host country. On the other hand, their illegality is often exploited by employers who exploit them. The two problems examined in this study are how the protection that International Law provides them and what solutions can be offered to migrant countries to cope with undocumented migrant workers. This research is normative research, with qualitative analysis. The results of this study show that International Law protects the rights of undocumented migrant workers who have carried out their work without discrimination. In the face of undocumented migrants’ preventive measures are better taken by the state than enforcement. Keywords: migrant workers, illegal, non-discrimination